Stalinism Revisited The Establishment of Communist Regimes in East-Central Europe - Tismaneanu, Vladimir (Central European University Press, 2009)
Deals with the period of takeover and of 'high Stalinism' in Eastern Europe (1945-1955). These years are considered to be fundamentally characterized by institutional and ideological transfers based upon the premise of radical transformism and of cultural revolution. Both a balance-sheet and a politico-historical synthesis that reflects the archival and thematic novelties which came about in the field of communism studies after 1989.